Adaptive anti-disturbance tracking control for nonlinear system with unknown control coefficient. (March 2017) - Sun, Haibin; Hou, Linlin
The tracking control problem for nonlinear system with unknown control coefficient and external disturbances is investigated in this article. By inspiring extended state observer and K filter, a novel extended state filter is first developed for state and disturbance observations. Then, by means of backstepping approach, an adaptive composite output feedback controller is constructed based on the state and disturbance estimations. The stability analysis is presented on the basis of the Lyapunov stability method. Finally, a numerical example is presented to demonstrate the effectiveness of the proposed control approach.